Light‐Induced Mott‐Insulator‐to‐Metal Phase Transition in Ultrathin Intermediate‐Spin Ferromagnetic Perovskite Ruthenates. Issue 12 (13th February 2023) - Liu, Ruxin; Si, Liang; Niu, Wei; Zhang, Xu; Chen, Zhongqiang; Zhu, Changzheng; Zhuang, Wenzhuo; Chen, Yongda; Zhou, Liqi; Zhang, Chunchen; Wang, Peng; Song, Fengqi; et al.
Abstract: Light control of emergent quantum phenomena is a widely used external stimulus for quantum materials. Generally, perovskite strontium ruthenate SrRuO3 has an itinerant ferromagnetism with a low‐spin state. However, the phase of intermediate‐spin (IS) ferromagnetic metallic state has never been seen. Here, by means of UV‐light irradiation, a photocarrier‐doping‐induced Mott‐insulator‐to‐metal phase transition is shown in a few atomic layers of perovskite IS ferromagnetic SrRuO3− δ . This new metastable IS metallic phase can be reversibly regulated due to the convenient photocharge transfer from SrTiO3 substrates to SrRuO3− δ ultrathin films. These dynamical mean‐field theory calculations further verify such photoinduced electronic phase transformation, owing to oxygen vacancies and orbital reconstruction. The optical manipulation of charge‐transfer finesse is an alternative pathway toward discovering novel metastable phases in strongly correlated systems and facilitates potential light‐controlled device applications in optoelectronics and spintronics. Abstract : A photocarrier‐doping‐induced reversible Mott‐insulator‐to‐metal phase transition is realized by means of UV‐light irradiation in a few atomic layers of intermediate‐spin ferromagnetic SrRuO3− δ . Dynamical mean‐field theory calculations further verify such photoinduced electronic phase transformation,  owing to oxygen vacancies and orbital reconstruction. Therefore, a new intermediate‐spin ferromagnetic metallic metastable phase of perovskite ruthenate is demonstrated.